2023
DOI: 10.3390/cancers15041228
|View full text |Cite
|
Sign up to set email alerts
|

Kisspeptin and GPR54 Receptor Expression in Endometrial Cancer Tissue

Abstract: Kisspeptin (KISS) is a natural peptide—discovered in 1996 as a factor inhibiting the ability to metastasize in malignant melanoma. This protein plays also a regulatory role in the process of puberty, the menstrual cycle, spermatogenesis, implantation and development of the human placenta. The present study aimed to evaluate the expression of KISS and its receptor GPR54 in endometrial cancer (EC) tissue, depending on the histological type of cancer, its stage, various demographic characteristics, and clinical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Kisspeptin levels during the periovulatory period are then high and ultimately initiate the LH surge associated with ovulation [ 41 ]. Besides, kisspeptin concentrations are associated with factors such as age, parity, adiposity, insulin sensitivity, and hormonal contraception [ 42 , 43 ]. Current reviews suggest that age impact on Kisspeptin and its receptor expression may be tissue-dependent and should not be correlated with the plasma level of kisspeptin [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Kisspeptin levels during the periovulatory period are then high and ultimately initiate the LH surge associated with ovulation [ 41 ]. Besides, kisspeptin concentrations are associated with factors such as age, parity, adiposity, insulin sensitivity, and hormonal contraception [ 42 , 43 ]. Current reviews suggest that age impact on Kisspeptin and its receptor expression may be tissue-dependent and should not be correlated with the plasma level of kisspeptin [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Besides, kisspeptin concentrations are associated with factors such as age, parity, adiposity, insulin sensitivity, and hormonal contraception [ 42 , 43 ]. Current reviews suggest that age impact on Kisspeptin and its receptor expression may be tissue-dependent and should not be correlated with the plasma level of kisspeptin [ 43 ]. It has been shown that Kisspeptin and Kisspeptin receptor can be found in many extrahypothalamic tissues and tumor cells [ 4 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations